Estudo da tratabilidade de efluentes de indústria de papel e celulose por microfiltração/ultrafiltração e processos oxidativos avançados - Saldanha, Theoana Horst (2019)
he proposal of this research was to evaluate the efficiency of two technologies for the posttreatment in two effluents from different companies – each effluent received a treatment alternative. In the first stage of the research the filtration experiments were carried out in a bench system, comparing the efficiency of microfiltration (MF) and ultrafiltration (UF) membranes. The experiments were conducted for 120 minutes at a pressure of 0.75 bar and Re 2243. The removal rates for color were 19.82% for MF and 15.74% for UF. For COD there was removal of 59.09% for MF and 57.60% for UF. Removal of the phenol was around 57-58% for both membranes. For ABS254 there was a reduction of 22.86 for MF and 19.76 for UF. The spectral area (200-800 nm) had a reduction of 19.34% for MF and 14.15 for UF. The results indicated that microfiltration and ultrafiltration membranes do not differ statistically from one another. The second stage of the research was to evaluate the efficiency of the advanced oxidative processes (OAP). The processes studied were: photo-Fenton and UV/ H2O2. The experiments were carried out in a 250 ml capacity photochemical reactor, the chemical reagents used were iron II heptahydrate (FeSO4. 7H2O) and hydrogen peroxide (H2O2). The operational conditions were adopted based on the studies of Neves (2017) that used 200 mg/l of H2O2 and pH 8 for the UV/H2O2 process and 5 mg/l of Fe2+ and 200 mg/l of H2O2 in the photo-Fenton process. The POA experiments lasted for 90 minutes and were submitted to artificial radiation. The removal values found for color were 89.51% for UV/H2O2 and 87.54% for Photo-Fenton. The results obtained for removal of COD were 71.05% for UV/H2O2 and 89.14% for PhotoFenton. The removal of phenol was in the range of 70-78% for both processes. Only the UV/H2O2 process obtained reduction to ABS254 of 86.5%. The reduction of the spectral area (200-800 nm) was 94.38% for UV/H2O2 and 75.3% for photo-Fenton. According to the data obtained in this step, the employed POAs demonstrated great potential as an post-treatment alternative, with the UV/H2O2 process being statistically superior in terms of efficiency in relation to photo-Fenton.